Pixel co-ordinate-based secret image sharing scheme with constant size shadow images. (January 2021) - Patil, Shravani Mahesh; B.R., Purushothama
Abstract: In this paper, we propose a secret image sharing scheme with constant size shadow images. In the proposed scheme, the size of the shadow images is 23 × 23 irrespective of the secret image size. The scheme also offers a lossless reconstruction of the secret image without requiring pre-sharing of a key between the share generator and combiner. The scheme is based on a multi-secret sharing scheme and uses pixel value co-ordinate sharing. We prove the security of the proposed secret image sharing scheme by reducing it to the underlying multi-secret sharing scheme. Finally, we evaluate the correctness of the scheme by conducting experiments on standard images. Graphical abstract: Highlights: In traditional image sharing schemes, shadow image size is a function of image size. Proposed secret image sharing scheme is first to offer constant size shadow images. The proposed scheme achieves a constant shadow image size of 23 × 23 pixels. The scheme is based on pixel coordinate sharing and offers lossless reconstruction. Proposed scheme does not require pre-shared key between share generator & combiner.